Pentingnya Pendidikkan Agama Kristen dalam Menerapkan Teori Bloom di Sekolah - Simatauw, Marfy (Sekolah Tinggi Teologi Borneo, 2025)
Abstract Christian Religious Education (PAK) in character building for students through the application of Bloom's theory. Bloom's taxonomy theory was developed by Benjamin Samuel Bloom, with learning objectives divided into three domains: Cognitive, related to thinking skills, such as remembering, understanding, applying, analyzing, evaluating, and creating. Affective, related to attitudes, values, interests, and emotions in learning. Psychomotor, related to physical skills. This demonstrates that education must be holistic, encompassing cognitive, affective, and psychomotor aspects, in line with the national education goal of developing individuals with faith and noble character. However, an imbalance has been found in the learning process, which focuses too much on the cognitive domain, neglecting students' character, spiritual, and physical development. This study aims to analyze the importance of applying Bloom's Theory in Christian religious education learning based on Deuteronomy 6:6-7, and to identify the impacts and challenges faced. Using qualitative descriptive methods with literature review, interviews, and field observations, this research is expected to provide more effective and systematic learning strategies. The integration of Bloom's Theory in Christian Religious Education is expected to enhance students' understanding of Christian values, develop better character, and build a strong community of faith. The data analysis concludes that the importance of implementing Bloom's Theory in learning can help students develop cognitive abilities more effectively and improve learning outcomes. Therefore, implementing Bloom's Theory also plays a role in enhancing students' critical thinking skills. Furthermore, the importance of implementing Bloom's Theory in every religious lesson is crucial, as it tends to be more systematic and able to accommodate various levels of student understanding, character, and talents. Keywords: Christian Religious Education, Bloom's Theory, Attitude Formation, Talent, Knowledge, Learning Abstrak Pendidikan Agama Kristen (PAK) dalam pembentukan karakter siswa melalui penerapan teori Bloom. Teori taksonomi Bloom di kembangan oleh Benjamin Samuel Bloom dengan tujuan pembelajaran ke dalam tiga domain sebagai berikut: Kognitif, berkaitan dengan kemampuan berpikir, seperti mengingatkan pemahaman, memahami, menerapkan, menganalisis, mengevaluasi, dan menciptakan. Afektif, berkaitan dengan sikap, nilai, minat, dan emosi dalam belajar. Psikomotorik, berkaitan dengan keterampilan fisik. Menunjukkan bahwa pendidikan Pendidikan harus holistik, mencakup aspek kognitif, afektif, dan psikomotorik, sejalan dengan tujuan pendidikan nasional untuk membentuk individu yang beriman dan berakhlak mulia. Namun, ditemukan ketidak seimbangan dalam proses pembelajaran yang terlalu berfokus pada ranah kognitif, mengabaikan pengembangan karakter, spiritual, dan jasmani siswa. Penelitian ini bertujuan untuk menganalisis pentingnya penerapan Teori Bloom dalam pembelajaran pendidikan agama Kristen berlandaskan Kitab Ulangan 6:6-7, serta mengidentifikasi dampak dan tantangan yang dihadapi. Menggunakan metode deskriptif kualitatif dengan studi pustaka, wawancara, dan observasi lapangan, penelitian ini diharapkan dapat memberikan strategi pembelajaran yang lebih efektif dan sistematis. Integrasi Teori Bloom dalam Pendidikan Aagama Kristen diharapkan dapat meningkatkan pemahaman siswa terhadap nilai-nilai Kristiani, membentuk karakter yang lebih baik, dan membangun komunitas beriman yang kuat. Dari hasil analisis data diperoleh bahwwa penerapan pembelajaran teori Bloom dapat tmembantu siswa mengembangkan kemampuan kognitif siswa secara lebih efektif dan meningkatkan hasil belajar yang baik, maka dengan menerapkan teori Bloom juga berperan meningkatkan daya pikir kritis siswa, serta pentingnya penerapan di setiap pembelajaran agama supaya teori Bloom cenderung lebih sistematis dan mampu mengakomodasi berbagai tingkat pemahaman, karakter dan bakat siswa. Kata Kunci: Pendidikan Agama Kristen, Teori Bloom, Pembentukan sikap, Bakat, Pengetahuan, Pembelajaran.